التأثير الوراثي الخموي لممستخمص المائي الخام لجذور نبات الفجل .Raphanus Sativus L على خلايا القمم النامية لجذور البصل .Allium Cepa L - السعدي رشا كريم محمد (Al-Nahrain Journal of Science, 2018)
This study was carried out to investigate the cytogenetic effects of crude extract from roots of Raphanus sativus L.(Brassicaceae) on the mitosis of root tips of Allium cepa L. using four concentrations (5,10,20 or 40)mg/cm3, for 4 hrs of treatment period. This study included some cytogenetic analysis such as mitotic index, phase index, chromosome aberrations index. Data showed that treatment with this extract led to reduce the mitotic index less than 50% when treated with 10, 40 mg/cm3 was 35.33% and 45.33%. This reduction considered to be toxic and sub lethal effects. Since it arrested the cells at metaphase in every treatments and caused chromosomal aberrations including sticky metaphase bridges, lagging chromosome, polar deviation in anaphase-telophase.